2021
DOI: 10.3390/ijerph18158028
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Alcohol Consumption Pattern Based on Gender during COVID-19 Confinement in Spain

Abstract: (1) The goal of this study was to analyze the prevalence and pattern of alcohol consumption (frequency of consumption, average daily consumption, and risky consumption) before and during confinement due to the coronavirus disease (COVID-19) in the adult population and based on gender. (2) Methods: Data from 3779 individuals were collected via a set of online surveys. The AUDIT alcohol consumption questions (AUDIT-C) were used to measure the frequency of consumption, the average daily consumption, intensive con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 28 publications
(43 reference statements)
3
15
0
Order By: Relevance
“…Specifically, the percentage of those who consumed alcohol four or more days a week was 1.5 times greater during confinement (11.54% vs. 17.57%) and more pronounced in the 18 to 44 age group. This finding nuances the decreases reported in young adults, indicating that a portion of consumers showed an increase in the frequency of alcohol consumption [21][22][23]. These cases could be related to the use of alcohol as a coping mechanism to deal with the stress associated with social isolation, insecurity, and economic hardship resulting from the COVID-19 pandemic [1,19,30,44,47,48].…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…Specifically, the percentage of those who consumed alcohol four or more days a week was 1.5 times greater during confinement (11.54% vs. 17.57%) and more pronounced in the 18 to 44 age group. This finding nuances the decreases reported in young adults, indicating that a portion of consumers showed an increase in the frequency of alcohol consumption [21][22][23]. These cases could be related to the use of alcohol as a coping mechanism to deal with the stress associated with social isolation, insecurity, and economic hardship resulting from the COVID-19 pandemic [1,19,30,44,47,48].…”
Section: Discussionmentioning
confidence: 59%
“…However, in this same age group, an increase in alcohol consumption, in terms of frequency and average amount, has also been reported [19,20], indicating that this could be a strategy used to cope with the stressful emotional burden of the pandemic [19]. Moreover, other studies report that, whereas part of the drinking population showed no change or less intake, another part showed an increase in consumption [21][22][23]. Finally, other studies report increases in alcohol consumption [24,25] and risky drinking [16], mostly in adults from 30 to 64 years old [14,26], with gender differences [22,27].…”
Section: Introductionmentioning
confidence: 58%
See 3 more Smart Citations